THE IMPORTANCE OF COMPLEX DEVELOPMENT OF MUSCLE GROUPS IN THE PROCESS OF PROFESSIONAL-APPLIED PHYSICAL TRAINING (Scientific journal of the Fergana State University, 2026)
This scientific work highlights the role of physical fitness in developing the motor capacity required for effective performance in professional and vocational activities. The study analyzes the historical approach through the example of the “master–apprentice” tradition, integrating it with modern requirements of physical education and sports pedagogy. Professional motor preparedness is divided into general and special stages, and the theoretical and practical foundations of forming these skills through physical exercises are presented. The article substantiates the importance of systematically developing the muscles of the neck, chest, back, abdomen, and legs through targeted exercises to enhance professional efficiency.